1999
DOI: 10.1074/jbc.274.33.23451
|View full text |Cite
|
Sign up to set email alerts
|

Active Site Residues of Human β-Glucuronidase

Abstract: Human ␤-glucuronidase (hGUSB) is a member of family 2 glycosylhydrolases that cleaves ␤-D-glucuronic acid residues from the nonreducing termini of glycosaminoglycans. Amino acid sequence and structural homology of hGUSB and Escherichia coli ␤-galactosidase active sites led us to propose that residues Glu

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 31 publications
(27 reference statements)
3
40
0
Order By: Relevance
“…Expression of the cDNA containing the E540A missense mutation in COS cells or insect cells produced an inactive protein with normal turnover and stability (43). These studies suggested that a transgene expressing human GUS E540A on the MPS VII (gus mps/mps ) background might provide a murine MPS VII model that retains the MPS VII phenotype, but has the added desirable feature of being immune tolerant to human GUS.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Expression of the cDNA containing the E540A missense mutation in COS cells or insect cells produced an inactive protein with normal turnover and stability (43). These studies suggested that a transgene expressing human GUS E540A on the MPS VII (gus mps/mps ) background might provide a murine MPS VII model that retains the MPS VII phenotype, but has the added desirable feature of being immune tolerant to human GUS.…”
mentioning
confidence: 93%
“…In prior work, we characterized the structure and active site of human GUS, and identified residue E540 as the active site nucleophile (42,43). Expression of the cDNA containing the E540A missense mutation in COS cells or insect cells produced an inactive protein with normal turnover and stability (43).…”
mentioning
confidence: 99%
“…Briefly, 200 bp of PKD1 promoter DNA (0.5 g) with the vector or CA-Mekk1 expression plasmids (0.2 g of DNA) with 80 pmol of scrambled siRNA, human p53 siRNA, or Mekk1 siRNA duplex in FBS and antibiotic-free medium was incubated, added to cells, and incubated overnight at 37°C. The medium was then replaced with fresh DMEM containing 2% serum and antibiotics, and the cells were harvested at 40 h. M-1 cells grown in DMEM/F-12 supplemented with 5% FBS, antibiotic, 1.5 mM Hepes, and 24 mM NaHCO 3 at 37°C were transfected with pEGFPN3 vector or kinase-dead CA-Mekk1 (DC) in the same vector using Lipofectamine and selected for neomycin (G418) resistance at a concentration of 400 g/ml as before (35). Mekk1 Ϫ/Ϫ and Mekk1 ϩ/ϩ mouse embryonic fibroblast cells were cultured in DMEM with 4.5 g/liter of glucose containing 10% (v/v) heat-inactivated fetal bovine serum (FBS) and antibiotic (100 IU/ml of penicillin, 100 g/ml of streptomycin).…”
Section: Methodsmentioning
confidence: 99%
“…The active site of human β-glucuronidase has been based on the experimentally determined active site in E. coli β-galactosidase and corresponds to the amino acid residues Glu451, Glu540 and Tyr504. The nature of the active site residues have been discussed previously (Islam et al, 1999).…”
Section: Introductionmentioning
confidence: 99%